Educational Supervision In Improving Teacher Professionalism At Sdn 005 Petapahan Jaya, Tapung District, Kampar District - Harlena, Harlena (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The research aims to describe the implementation of supervision to improve teacher professionalism. The research uses a qualitative approach with qualitative descriptive. The techniques used in collecting data are interview, observation and documentation techniques. The results of the research are that the first point is a) the supervisory role of the coordinating principal: b) the role of the principal as consultant, c) the third role is the principal as group leader, d) the role of the principal as evaluator. Then the second point is, the supporting and inhibiting factors faced in supervision activities by school principals show that: (1 support is sufficient information data, sufficient facilities, teachers are easy to manage. 2), namely: there is still a sense of fear that teachers have and even avoid when they want to be supervised, the principal is busy outside school hours, the age factor makes the teacher's understanding slow, and managing the right time is considered difficult